Late Barremian to early Aptian calcareous nannofossil paleoceanography and paleoecology from the Ocean Drilling Program Hole 641C (Galicia Margin) - F. TREMOLADA; T. J. BRALOWER; E. ERBA (Cretaceous Research, 2006)
Calcareous nannofossil assemblages at Site 641C (Galicia Margin, North Atlantic) were investigated in order to determine changes in fertility and temperature of surface waters. Taxa such as Zeughrabdotus spp. < 3.5 mu m, Biscutum constans, Discorhabdus rotatorius and Diazomatolithus lehmanii, which thrived in higher fertility conditions, are particularly abundant across the CM0 interval as opposed to those with oligotrophic affinities such as Watznaueria spp. and Nannoconus spp., which are generally reduced in abundance. The abundances of nannoconids are much lower than those observed in Tethyan sections, indicating higher fertility conditions. Slumpings and low recovery prevent the identification of the onset of the "nannoconid crisis", but a sharp drop in nannoconid abundances, observed prior to the CM0 interval, correlates with the "nannoconid decline" observed in several Tethys sections. The normalized ratio between low and high fertility taxa (Fertility Index) was used to characterize the nannofossil assemblages in terms of productivity changes. The highest values of the Fertility Index were observed across magnetic chron CM0. The paucity of cold water taxa such as Seribiscutum spp. and Repagulum parvidentatum suggests warm water conditions throughout the deposition of upper Barremian-lower Aptian sediments on the Galicia Margin. (c) 2006 Elsevier Ltd. All rights reserved.